1982
DOI: 10.1073/pnas.79.18.5547
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic variants are generated spontaneously at a high rate in mouse KHT tumor.

Abstract: Using the Luria-Delbruck fluctuation analysis, we have examined the lung tumor-forming ability of a series of parallel clones derived from the KHT tumor, grown to small defined sizes. From these studies, we conclude that metastatic variants arise spontaneously in the clonal lines during their growth, at an apparent rate of 10-5 per cell per generation. This rapid rate has implications for our understanding of tumor heterogeneity and the process of tumor progression. Previous (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 19 publications
3
76
1
Order By: Relevance
“…Consistent with a valid theory, the saltational multi-chromosomal theory of the origin of metastases would directly explain the peculiar kinetics of metastasis, namely, that they are unexpectedly "rapid" 43 or arise at "high rates" 44 and at "early and late stages of genetic divergence," 40 that they unpredictably change via "nonlinear progressions" 8,15 and follow a "nongenetic mechanism" 38 and "abrupt" 36 or "punctuated clonal expansions" 24 and generate "unpredictable" phenotypes 36,37 as originally described by Foulds and then in other studies listed in the Introduction.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 87%
See 2 more Smart Citations
“…Consistent with a valid theory, the saltational multi-chromosomal theory of the origin of metastases would directly explain the peculiar kinetics of metastasis, namely, that they are unexpectedly "rapid" 43 or arise at "high rates" 44 and at "early and late stages of genetic divergence," 40 that they unpredictably change via "nonlinear progressions" 8,15 and follow a "nongenetic mechanism" 38 and "abrupt" 36 or "punctuated clonal expansions" 24 and generate "unpredictable" phenotypes 36,37 as originally described by Foulds and then in other studies listed in the Introduction.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 87%
“…41 (8) Studying breast cancers, Navin et al advanced a phylogenetic theory that "tumors grow by punctuated clonal expansions-borrowing a term from species evolution to explain gaps in the fossil record," because metastasis could not be reconciled with the low rates predicted by "a linear progression model." 24 Animal studies have also shown "evolutions" of metastases 42 at "rapid" 43 or "high rates" 44 that exceed those of conventional mutations by orders of magnitude. [44][45][46] All these observations, including Foulds' rules, are hard to reconcile with the conventional view that metastases are end products of multiple steps of sequential mutations.…”
Section: Origin Of Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…2) and change phenotypes at rates that far exceed those at which genotypes and phenotypes are changed by conventional mutation [53][54][55]. For example, highly aneuploid cancer cells become drug resistant at rates of up to 10 Ϫ3 per cell generation [53,54,[56][57][58] or become metastatic at 'high rates' [59,60]. As a result of this inherent chromosomal instability most cancers are enormously heterogeneous populations of nonclonal and partially clonal, or sub-clonal cells [13,61].…”
Section: Karyotype-phenotype Variations At Rates That Are Orders Highmentioning
confidence: 99%
“…The mutation hypothesis has to assume mutation rates of up to 10 Ϫ3 per cell generation to explain the frequent, spontaneous variation of phenotypes in highly aneuploid cancer cells. Examples are the 'high rates', compared to mutation, at which some cancers generate metastatic cells [59,60], or generate drug-resistant variants [53,54,56,58]. But the mutation rates of most cancers are not higher than those of normal cells [6,19,20,47,66,[70][71][72][73][74].…”
Section: Appendixmentioning
confidence: 99%